EKO-INOVASI DALAM PARIWISATA PUSAKA: BAGAIMANA UMKM KULINER LOKAL DI PANGKEP MELESTARIKAN RASA MELALUI RESILIENSI EKO DIGITAL - Agung Muliaman Anas; Damas Gianlugi Alrizqi; Yulnita Muchtar (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
The integration of intangible cultural heritage preservation and environmental sustainability presents complex challenges for Micro, Small, and Medium Enterprises (MSMEs) in tourism destinations, particularly within conservation areas such as UNESCO Global Geoparks. This study aims to investigate the dynamics of eco-innovation in the traditional culinary sector of Pangkajene and Kepulauan (Pangkep) Regency, South Sulawesi. Employing a mixed-methods research design combining quantitative surveys and in-depth case studies, this research analyzes three primary heritage commodities: Dange cake, Milkfish (Bandeng) processing, and Sop Saudara. The findings reveal a strong "Authenticity Paradox," where Dange producers maintain wood-fired cooking methods to preserve authentic sensory profiles while incrementally adopting biodegradable packaging innovations. Conversely, the Milkfish processing sector demonstrates high adoption of the circular economy through the transformation of fish scale waste into value-added products. This research also introduces the concept of "Eco-Digital Resilience" as a novel adaptive mechanism, where supply chain digitalization is proven to enhance resource efficiency and facilitate the narrative marketing of green products. The study concludes that the success of eco-innovation in Geopark regions relies not on total technological substitution, but on a hybrid approach that harmonizes ecological efficiency with local wisdom values.